Mass land valuation serves as a prerequisite for optimizing the taxation system in Ukraine - Kuryltsiv, R.; Myronov, O. (Land Management, Cadastre and Land Monitoring, 2024)
The article highlights the issue of multiple tax base systems. It analyzes that according to existing international mass appraisal standards, the market value should serve as the tax base. In turn, determining the market value should be based on analyzing the most efficient use. The authors emphasize that the available information in state registers is insufficient to meet all the requirements for the integrity and quality of input data for mass appraisal systems. Thus, attention is drawn to the necessity of a comprehensive approach to implementing a cadastre system, including the use of the LADM standard. This standard would, on the one hand, systematize the exchange between existing state registers, and on the other hand, serve as a basis for developing a computerized mass appraisal system taking into account the requirements for CAMA. Overall, the authors believe that implementing a land mass appraisal system in Ukraine is an important step towards creating a transparent and fair tax system as a key element of economic recovery and a source of revenue for local budgets in the context of developing market land relations.